Mixed Cutaneous Infection Caused by Leishmania and Dermatophytes: A Rare Coincidence or Immunological Fact - Amresh Kumar Singh; Ankur Kumar; Jayesh Pandey; Vivek Gaur; Pratima Tripathi; Indra Prasad Adhikari (Hindawi Limited, 2021)
Leishmaniasis was first described in 1824, in the Jessore district of Bengal (now Bangladesh) and more prevalent in Bihar, Uttar Pradesh, Jharkhand, and West Bengal. The disease is associated with depressed cellular immunity. Tinea is a fungal infection of the skin, which can become more extensively pathogenic particularly in patients with depressed cell-mediated immunity. Regulatory T cells and Th17 cells have been shown to be responsible for post-kala-azar dermal leishmaniasis (PKDL). We present a rare case of a 52-year-old house wife with a history of recurrent itching, depigmentation of the skin of extremities, and loss of appetite for 2-3 months followed by progressive spread of such lesion all over the body in an apparently healthy female. On examination, there were many hypopigmented scaly lesions mainly over the extensor aspect of the body. Skin lesions were characteristics of tinea infection with or without PKDL. A diagnosis of PKDL with tinea was made based on the history of kala-azar and on the skin slit smear for amastigote forms, rK39 test, and KOH mount. Routine blood investigations showed negative serology for HIV and lower normal CD4+T counts. The patient was advised for treatment on systemic antifungal therapy with antihistaminics and later with miltefosine. We have highlighted that PKDL, although uncommon, is a distinct manifestation of VL. In our case study, we also tried to find the reason of coinfection; this was probably due to the depressed cellular immunity, skin abruptions, and acquired dermatophytic infection which is prevalent and associated with lower CD4+ T cell count.